2015 International Conference on Information Processing (ICIP) 2015
DOI: 10.1109/infop.2015.7489422
|View full text |Cite
|
Sign up to set email alerts
|

Detection of leukemia in microscopic white blood cell images

Abstract: Leukemia means blood cancer which is featured by the uncontrolled and abnormal production of white blood cells (leukocytes) by the bone marrow in the blood. Analyzing microscopic blood cell images, diseases can be identified and diagnosed early. Hematologist are using technique of image processing to analyze, detect and identify leukemia types in patients recently. Detection through images is fast and cheap method as there is no special need of equipment for lab testing. In this paper, we proposed a method of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…White blood cells (WBCs) are important immune cells in the human body, which are mainly involved in immune response and regulation of inflammation [ 1 ]. The three-type differential count of WBCs, i.e., monocyte, lymphocyte, and granulocyte, provides an important indication for the diagnosis of many diseases, such as leukemia [ 2 , 3 ] and cancers [ 4 ]. As the dominant fraction of granulocytes, neutrophils usually show an abnormal change in the expected number when dealing with damaged tissues and unresolved infections [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…White blood cells (WBCs) are important immune cells in the human body, which are mainly involved in immune response and regulation of inflammation [ 1 ]. The three-type differential count of WBCs, i.e., monocyte, lymphocyte, and granulocyte, provides an important indication for the diagnosis of many diseases, such as leukemia [ 2 , 3 ] and cancers [ 4 ]. As the dominant fraction of granulocytes, neutrophils usually show an abnormal change in the expected number when dealing with damaged tissues and unresolved infections [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Khobragade et al [10] demonstrated a technique of leukaemia detection in patients from testing the microscopic white blood cell images. The focus is on the variations in the geometry of cells and statistical parameters such as mean and standard deviation which differentiates the white blood cells from other blood components employing processing tools including MATLAB and Lab VIEW.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the proposed research work, rather than making use of the BBPSO algorithm, Bare-bones with Adaptive Bat Optimization (BBABO) is introduced for feature selection process. At last, the classification task is carried out by integrating both the Fuzzy Neural Network (FNN) and Enhanced Support Vector Machine (ESVM) classifiers [10] called as FNESVM.…”
Section: Introductionmentioning
confidence: 99%
“…Among thresholding methods, the Otsu's method is reported to be highly efficient. 5,6 An adaptive segmentation method for WBCs was proposed by Liu et al 7 This method utilizes the outstanding edge density and low intensity of WBCs to discriminate them from red blood cells. 7 Other than classic segmentation methods, classifiers are commonly used for direct detection of objects of interest.…”
Section: Introductionmentioning
confidence: 99%